We could say, hey, this is the same thing as y is equal to zero times x minus seven. And so now, it looks just like what we have over here and you might recognize that our y-intercept is negative seven, y-intercept is equal to negative seven. And our slope is a coefficient on the x term, it

The equation of the given function is: y = a (x - 1) (x - 2) (x - 3) Using the y-intercept formula, it can be obtained by substituting x = 0 in it. y = a (0 - 1) (0 - 2) (0 - 3) = -6a So the y-intercept is (0,